Epiregulin expression and secretion is increased in castration-resistant prostate cancer - Wiesehöfer, Marc; Raczinski, Benedikt Bernhard Gereon; Wiesehöfer, Caroline; Dankert, Jaroslaw Thomas; Czyrnik, Elena Dilara; Spahn, Martin; Kruithof-de Julio, Marianna; Wennemuth, Gunther (Frontiers in Oncology, 2023)
Introduction In prostate cancer, long-term treatment directed against androgens often leads to the development of metastatic castration-resistant prostate cancer, which is more aggressive and not curatively treatable. Androgen deprivation results in elevated epiregulin expression in LNCaP cells which is a ligand of EGFR. This study aims to reveal the expression and regulation of epiregulin in different prostate cancer stages enabling a more specific molecular characterization of different prostate carcinoma types. Methods Five different prostate carcinoma cell lines were used to characterize the epiregulin expression on the RNA and protein levels. Epiregulin expression and its correlation with different patient conditions were further analyzed using clinical prostate cancer tissue samples. Additionally, the regulation of epiregulin biosynthesis was examined at transcriptional, post-transcriptional and release level. Results An increased epiregulin secretion is detected in castration-resistant prostate cancer cell lines and prostate cancer tissue samples indicating a correlation of epiregulin expression with tumor recurrence, metastasis and increased grading. Analysis regarding the activity of different transcription factors suggests the involvement of SMAD2/3 in the regulation of epiregulin expression. In addition, miR-19a, -19b, and -20b are involved in post-transcriptional epiregulin regulation. The release of mature epiregulin occurs via proteolytic cleavage by ADAM17, MMP2, and MMP9 which are increased in castration-resistant prostate cancer cells. Discussion The results demonstrate epiregulin regulation by different mechanism and suggest a potential role as a diagnostic tool to detect molecular alterations in prostate cancer progression. Additionally, although EGFR inhibitors false in prostate cancer, epiregulin could be a therapeutic target for patients with castration-resistant prostate cancer.